The technique of three-component regional blockade of the anterior neck region as a component of anesthesia during operations on the thyroid and parathyroid glands - A. A. Alekseev; A. G. Yavorovskiy; E. N. Prazdnikov; A. M. Ovechkin; D. V. Dospekhov; V. S. Vakhromkin; E. A. Sozonova; E. V. Batulina; A. A. Maksimova; E. N. Zolotova (Вестник анестезиологии и реаниматологии, 2024)
Introduction. The use of various regional blockades as a component of general anesthesia reduces the risk of postoperative complications such as intense pain syndrome, postoperative nausea and vomiting, and postoperative cognitive dysfunction. The study is devoted to the development and description of the technique of regional anesthesia of the anterior surface of the neck during operations on the thyroid and parathyroid glands under ultrasound navigation.The objective was to develop a safe and effective technique of regional anesthesia for operations on the thyroid and parathyroid glands under ultrasound navigation.Materials and methods. The trial involved 60 patients operated on for thyroid and parathyroid gland diseases. All patients were randomized into two groups: group 1 – combined anesthesia: general anesthesia + three-component blockade of the anterior surface of the neck; group 2 – general anesthesia. In group 1, intermediate cervical plexus blockade, pericapsular thyroid blockade, and Berry’s ligament blockade were performed under the control of ultrasound navigation. The patients’ condition was evaluated preoperatively, intraoperatively and in the postoperative period (after 3 and 12 hours) according to the following parameters: hemodynamic variability, pain intensity according to the numerical rating scale, frequency of postoperative nausea/vomiting and postoperative cognitive dysfunction (MOCA, MMSE), terms of postoperative activation of patients, need for prescription of opioid and non-opioid analgesics after surgery.Results. The combination of general anesthesia and the technique of three-component regional neck blockade allowed to limit the use of opioid analgesics: opioid consumption in group 1 was 3.12 [2.68; 3.75] μg/kg, in group 2 – 5.93 [4.48; 7.21] μg/kg (p < 0.0001). A higher rate of cognitive recovery was noted in group 1 compared to patients in group 2 (p = 0.0114). Combined anesthesia provided a long pain-free period after surgery: 12 hours after extubation, patients in group 1 had a very low level of pain according to numerical rating scale – 0 [0; 6.0] mm, patients in group 2 had higher values – 14 [10; 18] mm. The use of regional blockade allowed to reduce ketoprofen consumption in the postoperative period (consumption in group 1 amounted to 1.85 [1.30; 2.02] mg/kg, in group 2 – 3.19 [2.58; 5.97] mg/kg (p = 0.0015)).Conclusion. General anesthesia with three-component regional blockade of the anterior surface of the neck during operations on the thyroid and parathyroid glands under ultrasound navigation is effective and safe technique.